Historical wealth accounts for Britain: Progress and puzzles in measuring the sustainability of economic growth - McLaughlin, E.; Hanley, N.; Greasley, D.; Kunnas, J.; Oxley, Leslie; Warde, P. (2014)
Estimates of Britain's comprehensive wealth are reported for the period 1760-2000. They include measures of produced, natural, and human capital, and illustrate the changing composition of Britain's assets over this time period. We show how genuine savings, GS (a year-on-year measure of the change in total capital and a claimed indicator of sustainable development) has evolved over time. Changes in total wealth are compared to alternative, investment-based measures of GS, including variants augmented with the value of exogenous technology. Additionally, the possible effects of population change on wealth, and the implications of including carbon-dioxide emissions in natural capital are considered. © The Authors 2014. Published by Oxford University Press.